Soil type and wetting intensity control the enhancement extent of N2O efflux in soil with drought and rewetting cycles - Panpan Jiao; Lei Yang; Zhongwu Li; Peng Zheng; Xiaodong Nie (International Soil and Water Conservation Research, 2024)
Climate change alters the intensity and frequency of drought and rewetting (D/W) events; however, the influence patterns of D/W on soil N2O efflux in the water-limited area were not fully understood. Therefore, the impacts of D/W cycles varying in different extent of rewetting and frequency to N2O efflux in two kinds of soil on the Loess Plateau were investigated. The incubation conditions consisted of 1) D/W treatments with four 7-day cycles from 10% water holding capacity (WHC) to 60%WHC or 90%WHC, 2) constant moisture of 60%WHC and 90%WHC. The pulse of N2O efflux rate under 10−60%WHC treatment was higher than that under 10−90%WHC treatment in calcic cambisols, while opposite trend was observed in earth-cumuli-orthic anthrosols. Meanwhile, the pulse of N2O efflux rate decreased as cycle number increased for different wetting intensities and soil types. The direct N2O efflux under 10−60%WHC and 10−90%WHC treatments were 5.49 and 1.89 μg N2O–N g−1 soil in calcic cambisols, with those being 1.92 and 10.85 μg N2O–N g−1 soil in earth-cumuli-orthic anthrosols, respectively. The N loss in earth-cumuli-orthic anthrosols was approximately 5.74 times greater than that in calcic cambisols under 10−90%WHC treatment, whereas the N loss under 10−60%WHC treatment was about 2.86 times greater in calcic cambisols than that in earth-cumuli-orthic anthrosols. This study suggested that extreme rainfall events can enhance the N2O efflux and N loss in agricultural soils on the Loess Plateau in terms of soil type and wetting intensity, which should not be ignored in the N fertilizer management.